Studi Kelayakan Investasi Mesin Stamping dan Usulan Tata Letak Fasilitas Mesin Produksi Spring Seat B: Studi Kasus : PT XYZ - Indra Permana, Davit; Murnawan, Hery (Fakultas Teknik UMRI, 2025)
This study evaluates the feasibility of investing in a 63-ton stamping machine to boost Spring Seat B production at PT XYZ, Kampung Logam, Ngingas, Waru. The old machine produced 4,000 units/day, making it difficult to meet targets and requiring overtime. The new machine, costing Rp65,257,000, doubles the capacity to 8,000 units/day. Investment analysis using Payback Period and Break Even Point (BEP) shows a payback in 68 days, with a BEP of 539,916 units. In 2025, total production costs reached Rp1,662,308,586 and revenue was Rp1,867,296,000, resulting in a net profit of Rp204,987,414.08. Layout improvements were also made by relocating the rotary machine closer to the repair tool room to reduce the process distance and improve efficiency.